1989
DOI: 10.1210/jcem-68-1-141
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Exercise Increases Serum Insulin-Like Growth Factor-Binding Protein Concentrations*

Abstract: We studied the response of serum 34K insulin-like growth factor-binding protein (IGF-BP) to two types of prolonged exercise. In the first study, 11 normal men performed cycle ergometer exercise, after an overnight fast, for 3 h at the intensity corresponding to 45-50% of their maximal aerobic power. After the exercise, the mean serum IGF-BP concentration was 4.9-fold higher than the baseline level (P less than 0.01), while the IGF-I concentration did not change. Resting for the same time period resulted in a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 21 publications
6
40
2
Order By: Relevance
“…Given the limited duration of exercise chosen for this study, it was thought unlikely that IGFBP-1 concentration would change (no effect was seen following 30 min of moderate exercise in a previous study (25)). IGFBP-1 concentration has, however, been shown to increase in response to exercise of longer duration or intensity (26,27). The production of IGFBP-1 by the liver is thought to be activated when circulating concentrations of metabolic substrates are low (28) and is also known to fluctuate dramatically according to insulin concentration (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited duration of exercise chosen for this study, it was thought unlikely that IGFBP-1 concentration would change (no effect was seen following 30 min of moderate exercise in a previous study (25)). IGFBP-1 concentration has, however, been shown to increase in response to exercise of longer duration or intensity (26,27). The production of IGFBP-1 by the liver is thought to be activated when circulating concentrations of metabolic substrates are low (28) and is also known to fluctuate dramatically according to insulin concentration (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical point of view, this makes IGFBP-1 at admission an interesting prognostic predictor, which also remained after multiple adjustment. IGFBP-1 has been described as the most likely acute regulator of IGF-I actions (25), and the hepatic production of IGFBP-1 is upregulated in response to proinflammatory cytokines (26) and physiological stresses (27) and is downregulated by insulin (13). There are several potential links between high levels of IGFBP-1 and increased cardiovascular risk.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…However, exercise has been reported to increase both IGFBP-3 concentrations and IGFBP-3 proteolytic activity (Suikkari et al 1989b), possibly resulting in enhanced uptake of IGF-I into tissues. It has been suggested that the IGFBPs, particularly IGFBP-3, may function as a reservoir for the IGFs.…”
Section: Storage and Transport Of Igfsmentioning
confidence: 99%